Indonesian Learning Through WhatsApp Group To Create Interactive Learning Conditions - Sugeng Santoso; Ni Komang Sarini Dewi (Journal of Digital Learning and Education, 2021)
Abstract: This research aims to use WhatsApp group to Indonesian learning in VIII class students at UPT SMP Negeri 3 Ponggok. This research used qualitative approach because it uses data in the form of words. At the same time, this research used experimental type because it is testing something. The research subjects were from VIII-D class students, and the object was Indonesian learning through WhatsApp group. The data collection techniques were observation, documentation, and questionnaires. Comparative analysis will be processed after the data is obtained. In addition, the analysis was also carried out with Miles and Huberman's technique. Miles and Huberman's technique has several stages; data reduction, data presentation, and drawing conclusions. The research resulted the use of WhatsApp group was more interactive and fun than another method that has been implemented before. Therefore it is increasing student learning outcomes. Keywords: Indonesian, interactive learning, WhatsApp group